The minimum age child imputability criminal in law peruana - Beraún-Sánchez, David B. (2019)
Criminal behavior not only being committed by older people; but these, at present, are made by teenagers, who not only perform trifie crimes as petty street theft. Teens are committing very serious criminal acts, including murder for profit, called killings. The research method used was descriptive, because we have sought and contemporary information collected, analyzed the problem investigated and explained the facts of reality, its implementation period is transverse; It is not experimental, since they have not been manipulated variables, but it is transactional, correlational and factual. The results show that: the delinquency rate in minors, regarding the crimes of murder for profit (killings) in the country, in 2013, do not exceed 1.38%; lawyers respondents in a 75.00% have said that the tiny teenage crime rate does not justify the modification of the law, because the index is not high commission of these criminal acts. The proposal of the Judiciary, to lower the age of criminal responsibility in the country, will not stop the criminal acts of adolescents, because the crime rate for adolescents in 2013, 1.38% is low, compared to what It occurs in other state, and it is not allowed to leave their commitments in this regard Peru has signed international treaties that make domestic law.